Bacterial xylanase supplementation improves nutrient utilization, gut integrity, and microbial metabolism in broilers fed energy-reduced diets - Benjaphorn Phusathian; Koonphol Pongmanee; Yongyuth Theapparat; Nanthawath Saikhwan; Tassanee Trairatapiwan; Chanporn Chaosap; Akaradet Seemacharoensri; G.B. Tactacan; Li-Yen Wong; Y. Ruangpanit (Poultry Science, 2026)
This study evaluated the effects of bacterial xylanase supplementation on growth performance, nutrient digestibility, intestinal integrity, and microbial metabolic function in broilers fed energy-reduced diets. A total of 1,050 one-day-old male Ross 308 broiler chicks were randomly assigned to three dietary treatments, each comprising 14 replicates of 25 birds: a positive control (CON; standard corn-soybean meal diet), a negative control with reduced energy (NC; -85 kcal/kg), and an energy-reduced diet supplemented with bacterial xylanase (NCX; 100 g/ton Belfeed Xylanase™). During the starter phase, broilers fed the NC diet exhibited higher feed intake and FCR compared with those fed the CON and NCX diets (P < 0.05), with no significant difference between the CON and NCX diets. Apparent digestibility of dry matter, crude protein, and fat did not differ among dietary treatments (P > 0.05). However, broilers fed the NCX diet showed higher (P < 0.05) digestibility of crude fiber, NDF, and ADF than those fed the CON or NC diets. Apparent metabolizable energy was higher in broilers fed the CON and NCX diets compared with the NC diet. Furthermore, broilers receiving the CON and NCX diets exhibited significantly lower serum fluorescein isothiocyanate-dextran concentrations than those fed the NC diet, indicating improved intestinal barrier integrity. Bacterial xylanase supplementation increased microbial alpha diversity and altered beta diversity clustering, with enrichment of beneficial taxa such as Bifidobacteriaceae and Lactobacillaceae. Functional metagenomic prediction suggested greater representation of carbohydrate metabolism and energy production pathways in the NCX diet, whereas the NC diet was associated with enrichment of stress-related and xenobiotic degradation pathways. Overall, bacterial xylanase supplementation mitigated the adverse effects of dietary energy reduction by improving fiber utilization, maintaining gut integrity, and modulating the cecal microbiota toward a more favorable metabolic profile.
Keywords: Animal Nutrition and Physiology; Aquaculture Nutrition and Growth; Rabbits: Nutrition, Reproduction, Health